Error Probabilities of Synchronous DS/CDMA Systems with Random and Deterministic Signature Sequences for Ideal and Fading Channels - Stokes, Jay; Ritcey, Jame A. (IEEE International Communications Conference ICC, 1996)
We present a software tool which eﬃciently computes the error probability of a direct sequence, code division multiple access (DS/CDMA) system. Several diﬀerent system models are analyzed including random signature sequences with ideal channels, deterministic signature sequences with ideal channels, random signature sequences with slowly fading channels, and deterministic signature sequences with slowly fading channels. We assume that the chips received from each of the multiple-access interference (MAI) sources are synchronous with the chips from a reference source. This provides an upper bound for an asynchronous DS/CDMA system. Numerical contour integration of the test statistic’s moment generating function (MGF) in the complex plane is used to eﬃciently evaluate the error probabilities.